Spatial Aspects in The Feasibility Study of Revitalization For Merdeka Field in Medan - Hendra Fahruddin Siregar (International Forum of Researchers and Lecturers, 2022)
The Feasibility Study of the Revitalization of the Merdeka Field in Medan City is to obtain a Foundation of the Planning and Design Program regarding the Development of the Merdeka Field Area in Medan City that meets the needs of the community as a nationally viable public facility. The feasibility study of the revitalization of Merdeka Field in Medan used primary data and secondary data. In the feasibility study of the revitalization of Merdeka Medan Field, it was analyzed through spatial aspects through Medan City Bylaw No.1 of 2022 concerning Regional Spatial Planning (RTRW) and Medan City Zoning Regulations from 2022 to 2042. The result of the feasibility study of the revitalization of Merdeka Field Medan is that the concept planned for the revitalization of Merdeka Square is in accordance with the Regional Spatial Plan (RTRW) of the city of Medan by remaining a Green Open Space (RTH) that functions as a catchment area. In addition, the Merdeka Square area also provides Blue Open Space (RTB) which can function as a medium for water storage and prevention of flooding.